Visible light-promoted reductive transformations of various organic substances by using hydroxyaryl-substituted benzimidazolines and bases. Issue 48 (1st December 2016) - Hasegawa, Eietsu; Izumiya, Norihiro; Fukuda, Takuya; Nemoto, Kazuki; Iwamoto, Hajime; Takizawa, Shin-ya; Murata, Shigeru
Abstract: Visible light promoted reduction reactions of organohalides, sulfonamides, organonitriles and epoxy ketones were performed using 1, 3-dimethylbenzimidazolines possessing 2-hydroxynaphthyl or 2-hydroxyphenyl substituents (HOAr-DMBIH) as photo-reductants. Xe or Hg–Xe lamp through an appropriate glass-filter (λ>390 nm) and a household white light-emitting diode were used as light sources. In these reactions, reductive cleavages of carbonhalogen, nitrogensulfur, carboncarbon (nitrile) and carbonoxygen bonds take place. Bases exert significant effects on the progress of these reactions in a manner that depends on the nature of the substrate. Addition of 1, 8-diazabicyclo[5.4.0]undec-7-ene as well as potassium t -butoxide significantly accelerates photo-reduction reactions of organohalides, sulfonamides and organonitriles while the decomposition of formed hydroxy ketones occurs in reactions of epoxy ketones. Single electron transfer from the photo-excited states of benzimidazolines (HOAr-DMBIH) or their deprotonated analogues ( − OAr-DMBIH) to the substrates is proposed to initiate these reactions. Graphical abstract: